2016
DOI: 10.1016/j.gendis.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of long non-coding RNAs in immune regulation

Abstract: Precise and dynamic regulation of gene expression is a key feature of immunity. In recent years, rapid advances in transcriptome profiling analysis have led to recognize long non-coding RNAs (lncRNAs) as an additional layer of gene regulation context. In the immune system, lncRNAs are found to be widely expressed in immune cells including monocytes, macrophages, dendritic cells (DC), neutrophils, T cells and B cells during their development, differentiation and activation. However, the functional importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 76 publications
(186 reference statements)
0
54
0
Order By: Relevance
“…Because the function of immune-related lncRNA has been discovered, lncRNA can interact with transcription factors and chromatin remodeling components (PRC2, WDR5). 47 A previous study from our laboratory demonstrated that the defect in SUV39H1/H3K9me3 is implicated in abnormal inflammation in COPD. 48 Thus, potential interactions of lnc-IL7R with SUV39H1 methyltransferase and other epigenetic regulators may be implicated in the regulatory mechanism, which warrants further elucidation.…”
Section: Discussionmentioning
confidence: 94%
“…Because the function of immune-related lncRNA has been discovered, lncRNA can interact with transcription factors and chromatin remodeling components (PRC2, WDR5). 47 A previous study from our laboratory demonstrated that the defect in SUV39H1/H3K9me3 is implicated in abnormal inflammation in COPD. 48 Thus, potential interactions of lnc-IL7R with SUV39H1 methyltransferase and other epigenetic regulators may be implicated in the regulatory mechanism, which warrants further elucidation.…”
Section: Discussionmentioning
confidence: 94%
“…FOXO1 suppressed cell metastasis by down-regulating AKT and inhibited lung cancer [16]. Hence, targeting lncRNAs could be considered as another approach to prevent and treat HCC [17][18][19][20]. According to previous study, it has been proved that LINC00668 is an oncogene in several cancers such as non-small-cell lung cancer [21] and gastric cancer then transferred to a polyvinylidene fluoride (PVDF) (Sigma-Aldrich).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs have low sequence conservation and mediate gene expression at post-transcriptional level through interaction with nucleic acids and proteins. And lncRNAs broadly participate in varied biological aspects, such as cell growth, differentiation, chromosome inactivation and even tumorigenesis [8][9][10][11]. In regard of cancer, an increasing amount of lncRNAs have been found to function as oncogenes or antioncogenes [12].…”
Section: Introductionmentioning
confidence: 99%